Plaque volume and occurrence and location of periprocedural myocardial necrosis after percutaneous coronary intervention: insights from delayed-enhancement magnetic resonance imaging, thrombolysis in myocardial infarction myocardial perfusion grade analysis, and intravascular ultrasound. - Porto, I; Selvanayagam, J; Van Gaal, W; Prati, F; Cheng, A; Channon, K; Neubauer, S; Banning, A (2006)
BACKGROUND: Myocardial necrosis can occur during percutaneous coronary intervention (PCI) despite optimal adjunctive pharmacology and careful technique. We investigated the mechanisms of procedural infarction using angiographic analysis, intravascular ultrasound, and delayed-enhancement magnetic resonance imaging. METHODS AND RESULTS: Fifty-two patients (64 vessels) who underwent complex PCI were studied. All patients were preloaded with clopidogrel and received glycoprotein IIb/IIIa inhibitors. "Adjacent" myonecrosis was defined as the presence of an area of new gadolinium hyperenhancement close to the stent. "Distal" myonecrosis was defined as situated at least 10 mm downstream from the stent. Fifteen vessels (23%) had evidence of new hyperenhancement after PCI. Of these, 8 (12%) had the distal type, and 7 (11%) had the adjacent type. Intravascular ultrasound showed a significantly greater reduction in plaque volume (91.6+/-51.5 versus 8+/-14 versus 20+/-35 mm3; P < 0.001) in the group with distal hyperenhancement compared with patients without new hyperenhancement or adjacent hyperenhancement. In the entire sample, a significant correlation was seen between changes in plaque volume (rho = 0.58, P < 0.001) after PCI and the mass of new necrosis measured by magnetic resonance imaging. Thrombolysis in Myocardial Infarction perfusion grade assessment of a closed microvasculature after PCI carried an odds ratio of 8.0 (95% confidence interval, 1.4 to 46.1; P = 0.02) for the occurrence of hyperenhancement, whereas side-branch occlusion was associated with an odds ratio of 16.2 (95% confidence interval, 2.6 to 102.5; P = 0.03). However, a closed microvasculature was associated with distal hyperenhancement (P = 0.02), and side-branch occlusion was associated with adjacent hyperenhancement (P < 0.001). CONCLUSIONS: These data suggest that distal embolization of plaque material occurs in contemporary PCI of native coronary arteries. Efforts to minimize procedural necrosis may require careful review of side branch anatomy and/or use of distal protection during extensive coronary stenting.